1993
DOI: 10.1177/0146167293196005
|View full text |Cite
|
Sign up to set email alerts
|

Dimensions of Contact as Predictors of Intergroup Anxiety, Perceived Out-Group Variability, and Out-Group Attitude: An Integrative Model

Abstract: This study tested an integrative model of how dimensions of contact (quantitative, qualitative, and intergroup) are related to intergroup anxiety, perceived out-group variability, and out group attitude. Data were collected in a field study of minority (Hindu) and majority (Muslim) religious groups in Bangladesh. Path analysis revealed that dimensions of contact were significant predictors of all three criterion variables, although different dimensions emerged as predictors in each case, and there were some in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

47
712
4
18

Year Published

1996
1996
2016
2016

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 677 publications
(781 citation statements)
references
References 32 publications
47
712
4
18
Order By: Relevance
“…In an attempt to identify moderators of threat responses, we assessed positive personal contact with African Americans using questions developed by Islam and Hewstone (1993), which assessed qualitative and quantitative out-group contact. We also assessed explicit racism (Modern Racism Scale [MRS]; McConahay, 1986), and the extent to which one was motivated to appear nonprejudiced (Motivations to Control Prejudice Reactions Scale; Dunton & Fazio, 1997).…”
Section: Background For the Present Researchmentioning
confidence: 99%
“…In an attempt to identify moderators of threat responses, we assessed positive personal contact with African Americans using questions developed by Islam and Hewstone (1993), which assessed qualitative and quantitative out-group contact. We also assessed explicit racism (Modern Racism Scale [MRS]; McConahay, 1986), and the extent to which one was motivated to appear nonprejudiced (Motivations to Control Prejudice Reactions Scale; Dunton & Fazio, 1997).…”
Section: Background For the Present Researchmentioning
confidence: 99%
“…La liste des conditions favorables ou nécessaires aux contacts intergroupes n'a cessé de s'allonger dans la deuxième moitié du 20 e siècle. Des auteurs comme Pettigrew (1998 ;Pettigrew et Tropp, 2008) et Dovidio, Gaertner et Kawakami (2003) ont effectué des recensions de ces éléments essentiels tels que : la gestion de l'anxiété causée par ces contacts (Islam et Hewstone, 1993 ;Wilder et Shapiro, 1989 ;Stephan et White Stephan, 1985) ; la fréquence et la durée des rencontres (Cook, 1984 ;Wilder et Thompson, 1980 ;Worchel, Andreoli et Folger, 1977 ;Zajonc, 1968) ; un contexte qui permet d'avoir des relations personnalisées (Brewer et Miller, 1988 ; la création d'une identité supra-ordonnée rassembleuse (Gaertner, Mann, Murrell et Dovidio, 1989 ;Gaertner et coll., 1994) ; et le caractère plaisant des rapports (Wilder, 1984). De même, les recherches récentes sur les contacts entre francophones et anglophones au Québec (Côté, 2005 ;Pagé, Côté et Lasry, 2007) montrent que ceux-ci ont des particularités liées au caractère linguistique de ces contacts, notamment l'importance du sentiment de compétence dans leur langue seconde sur l'anxiété des participants lors des contacts.…”
Section: La Théorie Des Contacts Intergroupesunclassified
“…Prior intergroup research guided by the Intergroup Contact Hypothesis has revealed the relationship between individuals' positive contact experiences with members of a different social group and intergroup attitudes toward that group (e.g., Islam & Hewstone, 1993;Voci & Hewstone, 2003). In essence, the more positive information individuals obtain about another social group through their positive contact experiences, the more positive intergroup attitudes can be expected.…”
Section: Interpersonal Consequences Of Intergroup Contact In Interculmentioning
confidence: 99%
“…The conceptualization and operationalization of contact quality, however, vary across studies. On the one hand, contact quality has been conceptualized in accord with Allport's optimal contact conditions (e.g., Islam & Hewstone, 1993;Voci & Hewstone, 2003). That being said, the majority of contact research has repeatedly applied status equality, cooperation, and intimacy as indicators of contact quality without much consideration for the characteristics of intercultural contact situations.…”
Section: Interpersonal Consequences Of Intergroup Contact In Interculmentioning
confidence: 99%
See 1 more Smart Citation